Proyeksi Harga Wajar Saham Perusahaan Jasa Sektor Properti, Real Estate, dan Konstruksi Bangunan - Sofi Zulfarida; Dedi Hariyanto; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the intrinsic value, condition of stock prices, the decision to be taken and to determine the projected fair price of the company's shares in the property, real estate, and building construction sectors listed on the Indonesia Eek Exchange (IDX). This research uses quantitative descriptive research. The data used in this study is secondary data, in the form of company financial statements and closing price. The population in this study is the construction and building subsector as many as 70 issuers. The sampling technique uses saturated sampling with a total sample of 30 issuers. The analysis technique used is fundamental analysis through the Price Earning Ratio (PER) approach and the concept of Time Value of Money with the absolute method of Discount Cash Flow (DCF). Research Results through the Price Earning Ratio (PER) approach show that there are 18 issuers with high stock price conditions (overvalued) and there are 12 issuers with low stock prices (undervalued). Research Results using the concept of Time Value of Money with the absolute method Discount Cash Flow (DCF) shows that there are 23 issuers that are in an undervalued position that can be bought and owned by new investors and there are 17 issuers that are in overvalued positions that should not be purchased by investors new. The most prioritized shares are the shares of PT Acset Indonusa Tbk (ACST) with the current market price of Rp. 2,460 and the projected fair price for the next 3 years (2020) is Rp. 6,383.03